2016
DOI: 10.1088/1367-2630/18/4/045003
|View full text |Cite
|
Sign up to set email alerts
|

Optimal bounds for parity-oblivious random access codes

Abstract: Random access coding is an information task that has been extensively studied and found many applications in quantum information. In this scenario, Alice receives an n-bit string x, and wishes to encode x into a quantum state r x , such that Bob, when receiving the state r x , can choose any bit Î i n [ ] and recover the input bit x i with high probability. Here we study two variants: parity-oblivious random access codes (RACs), where we impose the cryptographic property that Bob cannot infer any information a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
88
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(90 citation statements)
references
References 32 publications
2
88
0
Order By: Relevance
“…Recently, the authors of [37] have shown that evenparity-oblivious encodings are equivalent to the INDEX game, which implies 2 → 1 POM game is equivalent to the well known Bell-CHSH nonlocal game. Therefore, a quantum encoding of 2 → 1 POM with average success probability p Q exists only if a quantum strategy for playing the Bell-CHSH game with the same average success probability exists.…”
Section: Arxiv:150605174v2 [Quant-ph] 12 Sep 2015mentioning
confidence: 99%
“…Recently, the authors of [37] have shown that evenparity-oblivious encodings are equivalent to the INDEX game, which implies 2 → 1 POM game is equivalent to the well known Bell-CHSH nonlocal game. Therefore, a quantum encoding of 2 → 1 POM with average success probability p Q exists only if a quantum strategy for playing the Bell-CHSH game with the same average success probability exists.…”
Section: Arxiv:150605174v2 [Quant-ph] 12 Sep 2015mentioning
confidence: 99%
“…[45], we assume that all the security requirements (e.g., relativistic settings or experimental limitations) are already met, so that Bob does not have unlimited computational power to cheat within the BC stage. In this case, the validity of the no-go proofs of QOT [30][31][32][33][34][35][36][37][38] cannot be taken for granted, because all these proofs were derived without implying any limitation on the computational power of the cheater.…”
Section: Insecuritymentioning
confidence: 99%
“…Intriguingly, the conclusions of some of the no-go proofs [31][32][33][34][35][36][37] remain valid, that unconditionally secure QOT is still impossible in this case. The key reason is that secure BC, being not a BCCC, cannot avoid the participant keeping the commitment at the quantum level instead of taking a fixed classical value.…”
Section: Insecuritymentioning
confidence: 99%
See 2 more Smart Citations